METAFORA LIMA BUAH SAJAK SAPARDI DJOKO DAMONO DAN PENGGUNAANNYA DALAM PEMBELAJARAN SASTRA - Suyitno Suyitno (Universitas Negeri Makassar, 2023)
This study aims to review the semiotic technique of Sapardi's poetry in five selected poems from Sihir Hujan. This research is qualitative descriptive research. The analysis technique used is the semiotic theory with a heuristic-hermeneutic reading from Michel Riffaterre. Of the five poems that became the object of the study, it was found that almost all of them used implicit metaphors. Sapardi in Sihir Hujan relies on sound elements to form a rhythm, support the mood of the rhyme, and emphasize the meaning of the rhyme. Thus, it can be stated that the meaning of Sapardi's poem is something that is behind the textual expression of the poem. This study also came to the conclusion that the poem